Retinal nerve fiber layer thickness post-laser treatment in diabetic retinopathy: argon versus pattern scanning laser - Maimunah M,; Ropilah Abdul Rahman,; Othmaliza Othman,; Mushawiahti Mustapha, (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
Conventional argon laser causes transient thickening of retinal nerve fibre layer (RNFL). The effect of pattern scanning laser (PASCAL) has not been well described. We compared the immediate changes in peripapillary RNFL thickness post-panretinal photocoagulation between conventional argon lasers and PASCAL in patients with diabetic retinopathy changes. A total of 32 subjects were recruited. There were 16 patients in the argon group and 16 patients in PASCAL group. Diabetic patients were recruited from Ophthalmology Clinic, Universiti Kebangsaan Malaysia Medical Centre (UKMMC). Complete eye examinations and fundus photographs were performed at baseline prior to laser treatment, and post-laser treatment at two and four months. RNFL thickness was measured using time domain optical coherence tomography. Both groups were comparable with respect to clinical characteristics and demographics. There was no significant difference in average RNFL thickness between the two groups prior to treatment (p= 0.323). RNFL post-laser treatment for patients receiving conventional argon laser remained unchanged with no significant differences in all quadrants at any time-point (two and four months). However, for the PASCAL group, significant thickening occurred at four months for average RNFL and the inferior quadrant (p <0.05). The other quadrants similarly demonstrated increasing thickness at four months but this did not reach statistical significance. Transient RNFL thickening occurs in both conventional and PASCAL laser patients. The PASCAL laser induces a greater increase in RNFL thickness than the argon laser group. Important events, such as laser eye treatments and even type of laser used, are worthy of consideration when evaluating RNFL.